Synthesis and NMR of 4-Aryl-3,4-dihydrocoumarins and 4-Arylcoumarins - Sun, Jie; Wang, Yanfeng (Asian Journal of Chemistry, 2014)
This paper described the synthesis and 1H and 13C NMR chemical shifts of a series of 4-aryl-3,4-dihydrocoumarin and 4-arylcoumarin derivatives based on a combination of 1H and 13C NMR, HSQC and HMBC experiments.